2020
DOI: 10.1177/2150132720904181
|View full text |Cite
|
Sign up to set email alerts
|

Cerumen Management: An Updated Clinical Review and Evidence-Based Approach for Primary Care Physicians

Abstract: Objective: To provide family physicians with a practical, evidence-based approach to managing patients with cerumen impaction. Methods: MEDLINE, The Cochrane Library, and the Turning Research Into Practice (TRIP) database were searched for English-language cerumen impaction guidelines and reviews. All such articles published between 1992 and 2018 were reviewed, with most providing level II and III evidence. Results: Cerumen impaction is a common presentation seen in primary care and cerumen removal is one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 20 publications
0
21
0
6
Order By: Relevance
“…In some patients, the cerumen can be very hard and cannot be removed with cerumenolytics alone. In such patients, manual removal of impacted cerumen using syringing/suction/aspiration can be attempted in family practice with appropriate training 11 . Until now, there is no evidence on the efficacy of cerumenolytics followed by extraction procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In some patients, the cerumen can be very hard and cannot be removed with cerumenolytics alone. In such patients, manual removal of impacted cerumen using syringing/suction/aspiration can be attempted in family practice with appropriate training 11 . Until now, there is no evidence on the efficacy of cerumenolytics followed by extraction procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Cerumen impaction causes symptoms such as hearing loss, ear noise or ear pain and is a common reason for consultation in general practice. 1 , 2 About 5% of adults, 10% of children and one-third of geriatric and cognitively impaired individuals are affected. 3 , 4 Cerumen becomes drier at an older age due to atrophy of the cerumen glands.…”
Section: Introductionmentioning
confidence: 99%
“…This, together with the fact that hair in the ear canal becomes coarser with age, leads to a higher rate of cerumen impaction in elderly patients. 1 , 5 Furthermore, the natural self-cleaning mechanism can be inadequate and cerumen can become impacted, due to illness-related changes such as scaling skin disorders, for example, eczema and psoriasis, anatomical abnormalities of the ear canal and the routinely use of hearing aids or earplugs. 2 According to the Clinical Practice Guideline: Earwax (Cerumen Impaction) of the American Academy of Otolaryngology- Head and Neck Surgery , the following options are recommended for removing impacted cerumen: watchful-waiting, education, cerumenolytic agents, ear irrigation or other manual techniques for removing earwax (cerumen spoon, alligator forceps, suction, hook).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerumen type has been used by anthropologist to track human migratory patterns, such as those of Eskimas. 8 Further, the study of earwax has shown controversy, as some authors have suggested that earwax has high level of nutrients which help in microbial growth and other hold a view that earwax has some compounds that inhibit the growth of microorganisms and prevent ear infections. 9,10 Ear infection in any form has a varied microbial etiology, which influences the selection of an efficacious of anti-microbial agents.…”
Section: Introductionmentioning
confidence: 99%